A Multicentric Randomized Trial to Evaluate the ROle of Uterine MANipulator on Laparoscopic/Robotic HYsterectomy for the Treatment of Early-Stage Endometrial Cancer: The ROMANHY Trial - Gueli Alletti, Salvatore; Perrone, Emanuele; Fedele, Camilla; Cianci, Stefano; Pasciuto, Tina; Chiantera, Vito; Uccella, Stefano; Ercoli, Alfredo; Vizzielli, Giuseppe; Fagotti, Anna; Gallotta, Valerio; Cosentino, Francesco; et al. (Frontiers in Oncology, 2021)
Objective This prospective randomized trial aimed to assess the impact of the uterine manipulator in terms of lymph vascular space invasion (LVSI) in patients undergoing minimally invasive staging for early-stage endometrial cancer. Methods In this multicentric randomized trial, enrolled patients were randomly allocated in two groups according to the no use (arm A) or the use (arm B) of the uterine manipulator. Inclusion criteria were G1-G2 early stage endometrial cancer at preoperative evaluation. The variables collected included baseline demographic characteristics, perioperative data, final pathology report, adjuvant treatment, and follow-up. Results In the study, 154 patients (76 in arm A and 78 in arm B) were finally included. No significant differences were recorded regarding the baseline characteristics. A statistically significant difference was found in operative time for the laparoscopic staging (p=0.005), while no differences were reported for the robotic procedures (p=0.419). The estimated blood loss was significantly lower in arm A (p=0.030). No statistically significant differences were recorded between the two study groups in terms of peritoneal cytology, LVSI (p=0.501), and pattern of LVSI (p=0.790). No differences were detected in terms of overall survival and disease-free survival (p=0.996 and p=0.480 respectively). Similarly, no differences were recorded in the number of recurrences, 6 (7.9%) in arm A and 4 (5.2%) in arm B (p=0.486). The use of the uterine manipulator had no impact on DFS both at univariable and multivariable analyses. Conclusions The intrauterine manipulator does not affect the LVSI in early-stage endometrial cancer patients undergoing laparoscopic/robotic staging.